KEJADIAN HIPERTENSI DALAM KEHAMILAN DAN HUBUNGANNYA DENGAN TINGKAT KECEMASAN - Farida, Yuli; Mardianti, Mardianti (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2025)
Gestational hypertension is high blood pressure that occurs for the first time in the second trimester of pregnancy (after 20 weeks of gestation), where the systolic value is > 140 mmHg and systolic > 90 mmHg. Gestational Hypertension accompanied by urine protein is called preeclampsia. In Indonesia, preeclampsia or gestational hypertension is still a major problem of maternal mortality. Gestational hypertension is the first cause of maternal mortality in Indonesia at 33%. Although the cause of gestational hypertension is not yet known with certainty, many factors are thought to be related to the incidence of gestational hypertension, including the level of maternal anxiety. Anxiety in pregnant women if not handled seriously will have physical and psychological impacts and effects. The research aimed to determine the correlation between anxiety levels and the incidence of gestational hypertension in Karawang district. This research method uses a correlative analytical method with a case-control approach. The study population was all pregnant women with gestational age >20 mg in Karawang Regency. The sampling method used a Non-Probability Sampling technique with purposive sampling. Inclusion criteria: Gestational age >20 mg have an MCH book. The number of samples determined was 162 (81 case respondents and 81 control respondents). The result showed there was a significant correlation between anxiety levels and the incidence of gestational hypertension (p-value-0.000). It can be concluded that there was a correlation between anxiety levels and the incidence of gestational hypertension